Using a low-amplitude RF pulse at echo time (LARFET) for device localization in MRI - Tumer, Murat; Sarioglu, Baykal; Mutlu, Senol; Ulgen, Yekta; Yalcinkaya, Arda; Ozturk, Cengizhan (Springer Heidelberg, 2014)
We describe a new method for frequency down-conversion of MR signals acquired with the radio-frequency projections method for device localization. A low-amplitude, off-center RF pulse applied simultaneously with the echo signal is utilized as the reference for frequency down-conversion. Because of the low-amplitude and large offset from the Larmor frequency, the RF pulse minimally interfered with magnetic resonance of protons. We conducted an experiment with the coil placed at different positions to verify this concept. The down-converted signal was transformed into optical signal and transmitted via fiber-optic cable to a receiver unit placed outside the scanner room. The position of the coil could then be determined by the frequency analysis of this down-converted signal and superimposed on previously acquired MR images for comparison. Because of minimal positional errors (a parts per thousand currency sign0.8 mm), this new device localization method may be adequate for most interventional MRI applications.
Keywords: Interventional Mrı; Device Localization; Catheter Tracking; Frequency Down-Conversion; Self-Mixing; Magnetic-Resonance; Interventional Mri; Catheter Tracking; Transmission-Line; Invasive Devices; Fiducial Markers; Visualization; System; Probe; Accuracy